Physicians Skills Library - Sema Arıcı; Yıldız Kayalı; Fatma Selman (Journal of Medical Education and Family Medicine)
Objective: After graduation, physicians must be able to perform basic skills competently from their first year. However, it has been observed that physicians, especially in their first years, feel inadequate when performing some skills and perform them without self-confidence.The aim of our study is to enable students to develop their basic medical skills by practicing as much as they want and participating in the period they want (from Term 1 to Term 6) with the training program we have created under the name of the Basic Medical Skills Library and to enable them to perform their skills confidently, accurately and stress-free.Methods: A training program was created for Biruni University Faculty of Medicine students to practice in the basic medical skills section of the national core training program. Applications were received from students through a system, with a maximum of 15 people in a class, according to this curriculum. Students were given practical training after a short theoretical training. After the training, they were asked to complete an online survey.Results: Thirty-nine percent of the students who participated in the study were term 3 students, and 29% were term 2 students. The most frequently preferred applications by the students participating in the study are "Adult basic life support", "Ability to place and remove superficial sutures" and "Advanced cardiac life support in adults". All of the students said that they were satisfied with the open-door practice in which they participated. Eighty-three percent of the students who participated in the study answered "I strongly agree" to the question "I believe that I can better manage the patients I encounter with the practical training I received in the practice I attended."Conclusion: The results of the study revealed that the applications we made under the name "Basic medical skills library" increased the students' self-confidence in performing simple procedural skills and that they would be willing to perform these applications easily when necessary in their medical life.